Tren dan Evolusi Penelitian Terkait Pendidikan untuk Pembangunan Berkelanjutan: Sebuah Kajian Bibliometrik - Apia Agustin (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
As the need to face global challenges resulting from climate change increases, education plays an important role in forming individuals who are environmentally and socially responsible. Education for sustainable development is now the main focus of the global agenda to achieve the Sustainable Development Goals (SDGs). This research uses bibliometric analysis to identify and map various scientific articles, with the aim of determining topics, publishing journals, authors, frequently referenced articles, and the authors' countries of origin that discuss education for sustainable development. Additionally, this research will explore the literature's conceptualization, as well as intellectual and social structure. This bibliometric analysis includes 4,168 articles from 333 journals indexed in the Scopus database. Findings show that the first article on education for sustainable development published in a Scopus-indexed journal appeared in 1990. Since then, the number of publications has increased significantly, peaking in 2022 with an annual growth rate of 15.42%. This study emphasizes the importance of prioritizing implementation in higher education to form a more holistic and sustainable education system. It is hoped that further research will provide deeper insight into its application at various levels of education and in diverse contexts so that it can further contribute to achieving global sustainable development goals.